Marketing Through Video Blogs – An Emerging Trend - ROSE, DR.V.JOSEPHINE LOURDES DE; MS. THANGALAKSHMI, (The journal of contemporary issues in business and government, 2021)
Century filled with adventures incorporates various inventions in everyday chores. Every booming second, social media swirls as sixth-finger. Posting videos and photos in social media platforms is almost a fashion and video blogs (Vlogs) are interesting part that captures wide range of audience. Proliferation of Video blogs enhances common social interest that creates awareness about various new arrivals in the market. Watching Vlogs and following particular vlogger enables audience to identify several promotions made by them. Vlogs have made marketers job quite easier. Researchers have found that 53 percent of the customers engage in a brand after watching a video in social media and most of them are women. Therefore the study aims to identify the women perception towards Vlogs and promotions made by vloggers. A research was conducted during the period June- August2019 with a sample of 150 female respondents to identify the Vlogs frequently surfed by them and also their perception towards the emergent trend of marketing through internet. Several statistical tests such as chi square, ANOVA and factor analysis were performed to answer the research questions.